Children's Mental Health Is a Unique Risk Factor for Poor Academic Achievement: Results from a Longitudinal Study of Canadian Children - Tsar, Vasilinka (Université d'Ottawa / University of Ottawa, 2011)
Concurrent and prospective relationships between symptoms of depression, anxiety, attention deficit/hyperactivity disorder (ADHD), and conduct disorder (CD) and academic achievement were examined in a large sample of Canadian children. Students in Grade 5 (N = 715) completed the depression and anxiety subscales of the Behaviour Assessment System for Children – Second Edition. Parents reported on their child’s symptoms of ADHD and CD using the Brief Child and Family Phone Interview. Academic achievement was measured using teacher-rated learning skills and students’ grade point average (GPA) from their Ontario Student Record (OSR) in fifth grade and again in sixth grade (N = 627). Symptoms of depression, anxiety, ADHD, and CD were significantly negatively correlated with academic achievement at Time 1 and Time 2. After controlling for child’s sex, household income, maternal education, and days absent, children’s mental health problems accounted for an additional 12% and 11% of the variability in their Time 1 mean ratings of learning skills and GPA, respectively. Only symptoms of ADHD predicted Time 2 GPA (1% of the variance) after controlling for Time 1 GPA and other sociodemographic variables. Findings highlight the unique contribution of mental health problems in predicting academic achievement and point to the need to promote children’s mental health in schools.
Keywords: Children's mental health; Academic achievement